Anarchy in the USSR : a new beginning - Ruff, Philip (London : ASP, 1991)
Introduction / Philip Ruff -- Power to the people, not the party, first Congress of the KAS (Moscow, 1 May, 1989) -- What motivates us? / Andrei Isaev -- Second Congress of the KAS (Moscow, 24-25 March, 1990) -- From the editors of Obshchina -- Anarchists on Russian TV / Will Firth -- Anarchist stirrings in the USSR / Will Firth -- Anarchist murdered, KGB suspected -- The death of Piotr Siouda -- Workers' uprisings of the Sixties / Vadim Belotserkovsky -- Anarcho-syndicalist union formed -- Building a true workers' movement / Maxim Zhuraliev -- Communique of the SMOT -- The case of Victor Kassatkin -- Freedom for Lithuania: an open letter from Moscow -- The war against Iraq / Moscow KAS -- Declaration of principles / Moscow Union of Anarchists -- On the question of "sovereignties" / SMOT -- The Kronstadt Commune 70th anniversary international syndicalist conference (Moscow, 16-18 March, 1991) -- Anarcho-syndicalism in the USSR / K. ten Broke -- Interview with Vadim Damier (IREAN) -- Footnotes.
Keywords: Anarchism -- Soviet Union